An immission perspective of emerging micropollutant pressure in Luxembourgish surface waters: A simple evaluation scheme for wastewater impact assessment. (October 2019) - Gallé, Tom; Pittois, Denis; Bayerle, Michael; Braun, Christian
Abstract: While wastewater treatment plants have been identified as the most prominent source of emerging micropollutants in surface waters, prediction of their ambient concentrations remains a challenge. This is due to the variability of loads entering individual treatment plants and of the elimination capacity by the latter as well as potential attenuation in the river network. Although geospatially detailed models exist, they suffer from the same data input uncertainties. Here, we investigated the concentration profiles of 20 emerging pollutants in different river stretches in Luxembourg with variable sanitary pressures. Using carbamazepine as a recalcitrant wastewater indicator, the correlation of the compounds to the latter revealed source and fate variability as well as specific emitters. Relating carbamazepine to sanitary pressure, expressed as the sum of population equivalents in a catchment divided by its surface [PE ha −1 ] allowed predicting the impact of emerging pollutants on the entire river network. The limited variability of the pollutant profiles allowed for prioritization of impacted stretches depending on the different sanitary pressures at risk quotient exceedance. The main drivers of impact were triclosan, diclofenac, clarithromycine and diuron. Graphical abstract: Image 1 Highlights: In-stream screening of emerging pollutants allows for mitigation prioritization. Sanitary pressure as measure of dilution of wastewater pollutants in river networks. Pollutant-carbamazepine ratios reveal specific sources and fate variability. Impact assessment can be related to sanitary pressure and used for extrapolation. Abstract : Sanitary pressure expressed as population equivalents ha −1 is a straightforward indicator for emerging pollutant impact at any point in the river network.